Synthesis of Micro-encapsulated Phase Change Materials Using Chain Transfer Agent via Emulsion Polymerization - Choi, Sun (TMS 2020 149th Annual Meeting & Exhibition Supplemental Proceedings, 2020)
Microencapsulated phase change materials (MPCMs) are materials that store thermal energy, and emulsion polymerization is the preferred encapsulation method for their synthesis because it is economical and simple. In this work, we used the emulsion method to synthesize two different MPCMs, i.e., poly methyl methacrylate (PMMA) PCMs and PMMA-1-dodecanethiol (DDT) PCMs, by using 1-dodecanethiol as the chain transfer agent. To explore the effect of the chain transfer agent, the two MPCMs were characterized chemically, physically, and thermally by Fourier transform-infrared spectroscopy, optical microscopy, scanning electron microscopy, and differential scanning calorimetry. The analyses showed that 1-dodecanethiol promoted the uniform formation of spherical MPCMs by enhancing the stability of the oil– water interface of the emulsions. Also, 1-dodecanethiol was not included in the structures of the MPCMs, and it did not affect the thermal properties of the MPCMs, such as heat capacity and melting point, which demonstrated that the 1-dodecanethiol acted only as a surfactant.